2022
DOI: 10.1038/s42005-022-01111-x
|View full text |Cite
|
Sign up to set email alerts
|

An Ising machine based on networks of subharmonic electrical resonators

Abstract: Combinatorial optimization problems are difficult to solve with conventional algorithms. Here we explore networks of nonlinear electronic oscillators evolving dynamically towards the solution to such problems. We show that when driven into subharmonic response, such oscillator networks can minimize the Ising Hamiltonian on non-trivial antiferromagnetically-coupled 3-regular graphs. In this context, the spin-up and spin-down states of the Ising machine are represented by the oscillators’ response at the even or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has also been instrumental in understanding both equilibrium and nonequilibrium phenomena in statistical mechanics, as well as in tackling combinatorial optimization problems that defy traditional von Neumann computing architectures 26 . In the realm of optimization, the Ising model has been employed to describe the collective behavior of dissipatively coupled parametric oscillators (POs) [27][28][29][30][31] . Within this framework, studies have revealed that a network of resistively coupled electrical POs naturally converges towards a collective oscillation state that minimizes a Lyapunov function 32,33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been instrumental in understanding both equilibrium and nonequilibrium phenomena in statistical mechanics, as well as in tackling combinatorial optimization problems that defy traditional von Neumann computing architectures 26 . In the realm of optimization, the Ising model has been employed to describe the collective behavior of dissipatively coupled parametric oscillators (POs) [27][28][29][30][31] . Within this framework, studies have revealed that a network of resistively coupled electrical POs naturally converges towards a collective oscillation state that minimizes a Lyapunov function 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, studies have revealed that a network of resistively coupled electrical POs naturally converges towards a collective oscillation state that minimizes a Lyapunov function 32,33 . This allows the network to evolve towards the ground state configuration of its Hamiltonian, enabling the use of networks of POs to solve combinatorial optimization problems 27,29,[32][33][34] . While Ising systems formed by dissipatively coupled POs have been previously studied, only a few studies 28,33 have looked at the exploitation of the same dynamics exploited by these Ising systems in networks of POs coupled by dispersive frequency-dependent components, and these prior works are predominantly theoretical only.…”
Section: Introductionmentioning
confidence: 99%